AMIR AL-MU'MININ UMAR IBN KHATHAB : RAID AL-TAKHTHITH AL-LUGHAWI WA TA'RIB AL-TA'LIM - Jassem, Jassem Ali (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
This study attempted to investigate and unveil the linguistic planning among the Arabs in old times by reading available modern literature and references, and comparing them to what was written by Arab scholars in classical literary. The aim of the research was to see the beginning of linguistic planning among the Arabs, the implied topics in their books and scientific values. The result of the research showed the linguistic planning known by the Arabs before the advent of Islam, Quraish known political organization mentioned in the Koran, the codification of the Koran during the Prophet’s (peace be upon him) era, the order of Abu Bakr to Omar bin al-Khattab on arabization of education to other Arabic speakers, Omar bin Abdul ‘Aziz’s effort in codifying the Sunnah, and the innovation of Khalil ibn Ahmad Faraaheedi in prosody, and Qomoha and Benoit’s ways in correcting linguistic errors.DOI : 10.15408/a.v3i1.2910